2021
DOI: 10.1186/s13018-021-02370-0
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative treatment of insertional Achilles tendinopathy: a systematic review

Abstract: Background Insertional Achilles tendinopathy is difficult to manage, and there is no definite consensus on which nonoperative treatment is superior over the others. We aim to provide a clear summary of the best available evidence for nonoperative treatment specific to insertional Achilles tendinopathy. Methods Literatures were searched in PubMed, Embase, and Web of Science databases from inception to October 2020. The results were evaluated indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 41 publications
0
34
1
Order By: Relevance
“…Our results for ins-AT are not supported by two recently published systematic reviews [ 52 , 53 ] which indicate that adding ESWT to an eccentric loading program increases outcomes for ins-AT. As these two reviews included primary studies with predominantly lower evidence levels such as retrospective and prospective cohort studies, case series, case control studies and pilot studies, this may have contributed to different outcomes compared to our review.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results for ins-AT are not supported by two recently published systematic reviews [ 52 , 53 ] which indicate that adding ESWT to an eccentric loading program increases outcomes for ins-AT. As these two reviews included primary studies with predominantly lower evidence levels such as retrospective and prospective cohort studies, case series, case control studies and pilot studies, this may have contributed to different outcomes compared to our review.…”
Section: Discussioncontrasting
confidence: 99%
“…Mid-AT appears to involve isolated tendon pathology, in contrast to ins-AT [ 13 , 67 ]. It is possible that ESWT is less effective in treating certain non-tendinous tissues, as ins-AT may be accompanied by metabolic diseases [ 52 ], and often includes pathology in adjacent bursae and bone tissue, making the source of pain difficult to diagnose [ 13 , 68 , 69 ]. In particular, intratendinous bone formation in ins-AT is considered difficult to treat [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…For IAT, studies demonstrate a wide range of effectiveness, from 28 to 83%. 7,8 On average, about 45.6% of patients endorsed an excellent or good outcome in a recent meta-analysis. 8 ESWT is a modality in which pressure waves outside the body are delivered to damaged tissue to reduce pain and promote healing.…”
Section: Nonsurgical Managementmentioning
confidence: 99%
“…7,8 On average, about 45.6% of patients endorsed an excellent or good outcome in a recent meta-analysis. 8 ESWT is a modality in which pressure waves outside the body are delivered to damaged tissue to reduce pain and promote healing. ESWT was directly compared with eccentric strengthening for IAT by Rompe et al 7 in a level 1 study and found to be more effective at improving pain (64% versus 28%).…”
Section: Nonsurgical Managementmentioning
confidence: 99%
See 1 more Smart Citation